Avaliação da suplementação materna com óleo de chia sobre parâmetros metabólicos em modelo de restrição alimentar - Leão, Estéfany Ribeiro (2021)
Maternal nutrition and fatty acids consumption during gestational and/or lactational periods are critical determinants strongly related to normal fetal and postnatal development. Changes in offspring nutrition in the early stages of life may predispose to the development of metabolic disorders. In this sense, compounds that act in preventing and/or reversing these disorders have been sought. Chia oil (ChO) stands out as a promising food for having a high content of alpha-linolenic acid (55-66%), and phenolic compounds. The aim of this study is evaluate the influence of maternal supplementation with ChO by two doses (2.5 or 5g/kg bodyweight) over metabolic parameters in BALB/c mice subject to postnatal undernutrition. All procedures were approved by the local ethical committee for animal research. Thirty BABL/c mice were used. The females receive the supplementation with oil by gavage (2.5 or 5g/kg b.w.), since mating until weaning of the offspring. The neonatal undernutrition was induced by increasing litter size to 15-16 animals, forming the Undernutrition (UN), UN + chia oil (UN 2.5 or UN 5g/kg b.w.) groups. Litters with 8-10 animals were used as Control (C), without supplementation. The body weight was measured at 21, 70 and 120 days, and food intake was measured weekly after weaning. The oral glucose tolerance test (OGTT) was performed at 70 and 120 days of age of the offspring. After euthanasia (120 days), the tissues and blood were collected to analyses. Hepatic lipids were extracted by Folch’s method and evaluated by commercial kits. Plasma lipids and fasting glucose were also analyzed by commercial kits. Oxidative stress markers (TBARS and hidroperoxydes contents) and antioxidant enzymes (SOD and CAT) were determined by colorimetric method. All statistical analyses were conducted using GraphPad Prism® software, differences between groups were evaluated by one-way analysis of variance (ANOVA). The significance level adopted was p<0.05. At 21 days, the UN, UN 2.5 and UN 5 groups showed lower body weight, a higher weight gain and a lower weight of epididymal and retroperitoneal adipose tissue compared to Control. At OGTT 120 days the animals UN 2.5 and UN 5 showed a smaller area under curve compared to UN group. The UN 5 animals showed higher concentration of fasting glucose in comparision to C animals, and presented lower content of hepatic lipids compared to C, UN and UN 2,5 groups. The oxidative stress markers (TBARS) in liver were reduced in both groups supplemented, and the UN 2.5 showed higher CAT activity compared to control. Regarding the oxidative stress in the epididymal adipose tissue (EAT), the two supplemented groups had lower TBARS values compared to C, the hydroperoxide content was higher in the SOC 2.5 group compared to C and S, the UN 5 group showed lower content of hydroperoxide compared to UN 2.5 group, and the CAT activity was higher in the S and SOC 2.5 groups compared to the control. Thus, within the doses used in this study, it was noticed that maternal supplementation of chia oil at a dose of 5g/kg of body weight had a slight advantage, as it attenuated some metabolic parameters in undernourished animals, such as glycemic curve and reduced TBARS in the liver and TAE, demonstrating that chia oil at this dose can improve metabolic changes generated by neonatal malnutrition.